Micro Plastic Pollution in South Asia: The Impact of Micro Plastic Pollution Over the UN Sustainable Development Goals - Rifa, Tasfiea Rahman; Hossain, Mohammad Belayet (2022)
One of the most pressing environmental issues facing the world right now is plastic waste. Once in the environment, plastics continuously degrade into microplastics, which are fragments of plastic. There are more national and international promises to reduce microplastic pollution as the world's plastic production rises. National governments are increasingly banning single-use plastic products or imposing taxes on them. Consider the UN Sustainable Development Goals, the UN Environment Assembly Resolutions on Marine Litter and Microplastics and Addressing Single-Use Plastic Products Pollution as examples of these commitments. In 2015, the UN announced the adoption of 17 Sustainable Development Goals (SDGs). In an effort to increase their sustainability, the SDGs have been extensively adopted by governments and businesses. There are 17 SDGs, comprising 169 targets, which are measurable against 247 unique indicators but there is only one indicator under Goal 14, specifically related to reducing impacts from microplastics. There are various international and regional legal policies which have provisions that indicate plastic pollution but none of them have mentioned microplastic pollution. This paper briefly discusses the concept of microplastics and the situation of microplastics pollution in selected South Asian countries including India, Bangladesh, Maldives, Sri Lanka and Pakistan. The paper also analyses the impact of micro plastic pollution over Un Sustainable Development Goals. The research has been accomplished mainly by adhering to Doctrinal and qualitative research methods has been piloted based on library-based study. For the purpose of obtaining an effective research outcome, data have been gathered from the legal journals, several international documents including UN reports, articles and related books, newspaper articles, websites, Concluding Observations etc.